(untitled) - Rymes, Betsy (Cresskill, N.J., 2008)
This book provides teachers with the tools to analyze talk in their own classroom. With extrodinary ease, the author makes complex theoretical and methodological tools accessible to teachers. The author provides an inviting way in to the wondrous world of language in use that will remind teachers who are facing unprecedented outside pressures why they became teachers in the first place
Keywords: Phân tích tương tác trong giáo dục,Interaction analysis in education